2018
DOI: 10.1155/2018/1275486
|View full text |Cite
|
Sign up to set email alerts
|

Antichronic Gastric Ulcer Effect of Zinc-Baicalin Complex on the Acetic Acid-Induced Chronic Gastric Ulcer Rat Model

Abstract: Background Baicalin (BA) has been shown to have anti-inflammatory and antioxidant activity. Zinc is a nutrient element. Objective This study is aimed at investigating the antichronic gastric ulcer activity of Zn-Baicalin complex (BA-Zn) and its related mechanisms in an acetic acid-induced gastric ulcer rat model. Results The severely ulcerated gastric mucosa of model rats had lower GSH-Px (52.21 ± 7.13) and SOD (7.03 ± 0.10) activity, and higher MDA (2.39 ± 0.03) content compared to sham rats. BA-Zn reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In addition, the Zinc–Baicalin (BA–Zn) complex was evaluated in the acetic acid model in rats, showing significant anti-inflammatory and antioxidant effects. BA-Zn (6.5 and 13 mg/kg) increased SOD activity and GPx level and reduced the MDA content and IL-8 and TNF-α levels in the gastric mucosa [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Zinc–Baicalin (BA–Zn) complex was evaluated in the acetic acid model in rats, showing significant anti-inflammatory and antioxidant effects. BA-Zn (6.5 and 13 mg/kg) increased SOD activity and GPx level and reduced the MDA content and IL-8 and TNF-α levels in the gastric mucosa [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their development involves changes in the levels of PGE 2 , NO, growth factors, and cytokines, as well as changes in the microcirculation and the mucus adhesion pattern [ 171 ]. Rutin [ 65 ], hesperdidin [ 121 ], chrysin [ 90 ], and baicalin [ 85 ] showed antiulcerogenic and healing activity in this model; it can be inferred that flavonoids were able to accelerate the healing of ulcers, thereby being an important mechanism to reduce disease recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Herbs represent excellent resources for cost-effective and readily available gastro-protective remedies without significant side effects [14,15,16,17]. Medicinal/herbal plants and extracts represent some of the most attractive resources of new drugs and have shown promising results for the treatment of gastric ulcers [17,18,19,20,21,22,23,24]. The natural products obtained from medicinal plants, including flavonoids, polyphenols, terpenoids [18], saponins [24], alkaloids [12], and mucilaginous polysaccharides [25], show immense pharmacological significance such as anti-inflammatory, antimicrobial, antiulcer, anti-oxidant, and anticancer activities [24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…SOD, CAT and GSH constitute an endogenous antioxidant system, which can be used to remove excess oxygen-derived free radicals and maintain them at physiological levels [32]. GSH-Px also plays an important role in protecting against oxidative gastric mucosal injury [33]. In this experiments, we rstly showed that ethanol administration clearly altered the gastric mucosa by macroscopic evaluation of gastric lesions, and the NRNC-CDs signi cantly reduced the areas of gastric ulcer formation and ulcer index, suggesting the ability of these CDs in protecting gastric ulcer.…”
Section: Discussionmentioning
confidence: 99%